Rincones de aprendizaje y su influencia en el rendimiento académico de los estudiantes de 5to año de EGB de la Unidad Educativa Eneida Uquillas de Rojas. - Murillo Solís, Stibalys Pamela (2023)
Learning corners are those spaces designed by the teacher and are located in the classroom. They contain teaching materials that promote student learning. These corners are designed according to the different areas of knowledge that are taught in the classroom and promote constructivist and collaborative learning. For this reason, the main objective of this research is to determine the influence of the learning corners on the academic performance of the 5th year EGB students of the Eneida Uquillas of Rojas Educational Unit. The methodology used in the case study follows a mixed approach; While the research was descriptive, field and explanatory, inductive and deductive methods were also used, the population and sample are represented by the teacher and the 35 students of the 5th year of Basic General Education parallel "A" of the Eneida Educational Unit Uquillas de Rojas, it is important to mention that to obtain relevant information on the topic, two techniques were used: a survey, directed at the 35 students, and an interview with the teacher. The results were that the 5th year of EGB does not have learning corners that improve student performance, since these spaces do not have the necessary materials to promote meaningful learning, it is important to highlight that creativity and innovation play an important role in the creation of these corners.